Factors affecting conversion rates in laparoscopic cholecystectomy: a single surgeon study - Moger, Jayant; Badiger, Suresh (International Surgery Journal, 2020)
Background: There is need for conversion in laparoscopic cholecystectomy (LC) in some special situation to open cholecystectomy (OC) in order to minimize intraoperative and post-operative complications. The risk factors may be patient related, the gallbladder’s pathology and the surgeon. Most studies with regards finding the risk factors for conversion in LC involved multiple surgeons which is one of the factors. Our study is prospective study where in all cholecystectomy were done by the single surgeon so as to find out other risk factors for conversion. Methods: This was a prospective study conducted between January 2017 to 2020, where in a total 152 patients posted for LC and 27 got converted to OC. The factors analyzed were the age and sex of the patient, elective or emergency surgery, acute or chronic cholecystitis, comorbid conditions, previous abdominal surgery, post endoscopic retrograde cholangiopancreatography, intra operative adhesions, intraoperative complication like bile duct injury, bleeding from cystic artery or gall bladder bed, bile leak. Results: Out of 152 patient 27 (17.8%) got converted to open cholecystectomy. Mean age was 48.86 with lowest 15 and highest age operated was 83 years, among them 63 (41.4%) were male and 89 (56.8%) were female. Fibrosis at Calot’s triangle, intraoperative adhesions, cirrhosis of liver and age older than 60 years, were all signiﬁcantly correlated with an increased conversion rate to laparotomy. Conclusions: The risk factors may help to predict the diﬃculty of the procedure. This would permit the surgeon to better inform patients about the risk of conversion from laparoscopic to open cholecystectomy.